2019
DOI: 10.1088/1742-6596/1194/1/012041
|View full text |Cite
|
Sign up to set email alerts
|

Drinfel’d double structures for Poincaré and Euclidean groups

Abstract: All non-isomorphic three-dimensional Poisson homogeneous Euclidean spaces are constructed and analyzed, based on the classification of coboundary Lie bialgebra structures of the Euclidean group in 3-dimensions, and the only Drinfel'd double structure for this group is explicitly given. The similar construction for the Poincaré case is reviewed and the striking differences between the Lorentzian and Euclidean cases are underlined. Finally, the contraction scheme starting from Drinfel'd double structures of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…It can be shown by an explicit calculation that (6.23) satisfies the Fock-Rosly conditions. The r-matrices associated with all possible Drinfeld double structures on the D = 3 Poincaré algebra were recently classified in [18,35], where it was found that there are eight inequivalent D = 3 Poincaré Drinfeld doubles. In terms of the Stachura classification from subsection 5.2, four of them lead to the r-matrices of the type r 6 with = ±1 (and appropriate θ µν ), two have the r-matrix of the type r 2 with = β = 1 (and appropriate θ, θ ), and the remaining two Drinfeld double r-matrices are of the types r 1 with β = 1 and r 7 , respectively.…”
Section: Jhep09(2020)096mentioning
confidence: 99%
“…It can be shown by an explicit calculation that (6.23) satisfies the Fock-Rosly conditions. The r-matrices associated with all possible Drinfeld double structures on the D = 3 Poincaré algebra were recently classified in [18,35], where it was found that there are eight inequivalent D = 3 Poincaré Drinfeld doubles. In terms of the Stachura classification from subsection 5.2, four of them lead to the r-matrices of the type r 6 with = ±1 (and appropriate θ µν ), two have the r-matrix of the type r 2 with = β = 1 (and appropriate θ, θ ), and the remaining two Drinfeld double r-matrices are of the types r 1 with β = 1 and r 7 , respectively.…”
Section: Jhep09(2020)096mentioning
confidence: 99%
“…In contrast, as we commented at the end of Section 2.3, in lower dimensions, such structures do exist and the classification of Drinfel'd doubles was recently performed for the (2 + 1)D Poincaré [127] and 3D Euclidean algebras [128]. Moreover, to the best of our knowledge, the classification of Drinfel'd doubles for the (anti-)de Sitter algebras has only been carried out in (2 + 1) dimensions [115].…”
Section: Drinfel'd Double Structures For Cayley-klein Algebrasmentioning
confidence: 94%
“…We recall that the classifications of non-isomorphic 4D and 6D real Drinfel'd double structures were carried out in [124] and [125], respectively, while their Hopf algebra quantizations were constructed in [126]. From these results, and also from [54], there were obtained the classifications of Drinfel'd double structures for the (2 + 1)D (anti-)de Sitter algebras in [115], (2 + 1)D Poincaré algebra and centrally extended (1 + 1)D Poincaré algebra in [127] and 3D Euclidean algebra in [128].…”
Section: Drinfel'd Double Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…We recall that the classifications of non-isomorphic 4D and 6D real Drinfel'd double structures were carried out in [120] and [121], respectively, while their Hopf algebra quantizations were constructed in [122]. From these results and also from [50], there were obtained the classifications of Drinfel'd double structures for the (2+1)D (anti-)de Sitter algebras in [111], (2+1)D Poincaré algebra and centrally extended (1+1)D Poincaré algebra in [123], and 3D Euclidean algebra in [124]. By contrast, results concerning Drinfel'd double structures in the (3+1)D case are very scarce, only covering the real so(5) and anti-de Sitter so(3, 2) algebras given in [125].…”
Section: Drinfel'd Double Structuresmentioning
confidence: 99%